Double Ectopic Thyroid Gland in a 10-Year-Old Filipino Boy - Tomas Joaquin C. Mendez; Cecilia Gretchen Navarro Locsin (Philippine Journal of Otolaryngology Head and Neck Surgery, 2018)
Objective:                   To present a case of a double ectopic thyroid gland in a 10-year old boy and discuss the pros and cons of the different management options that were available.